Motor-Unit Number Estimation Is Sensitive in Detecting Motor Nerve Involvement in Patients with Carpal Tunnel Syndrome - SÜNTER, GÜLİN; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (KOREAN NEUROLOGICAL ASSOC, 2016)
Background and Purpose We compared the motor-unit number estimation (MUNE) findings in patients who presented with signs and/or findings associated with carpal tunnel syndrome (CTS) and healthy controls, with the aim of determining if motor-unit loss occurs during the clinically silent period and if there is a correlation between clinical and MUNE findings in CTS patients. Methods The study investigated 60 hands of 35 patients with clinical CTS and 60 hands of 34 healthy controls. Routine median and ulnar nerve conduction studies and MUNE analysis according to the multipoint stimulation method were performed. Results The most common electrophysiological abnormality was reduced conduction velocity in the median sensory nerve (100% of the hands). The MUNE value was significantly lower for the patient group than for the control group (p=0.0001). ROC analysis showed that a MUNE value of 121 was the optimal cutoff for differentiating between patients and controls, with a sensitivity of 63.3% and a specificity of 68.3%. MUNE values were lower in patients with complaints of numbness, pain, and weakness in the median nerve territory (p<0.05, for all comparisons), and lower in patients with hypoesthesia than in patients with normal neurological findings (p=0.023). Conclusions The MUNE technique is sensitive in detecting motor nerve involvement in CTS patients who present with sensorial findings, and it may be useful in detecting the loss of motor units during the early stages of CTS. Larger-scale prospective clinical trials assessing the effect of early intervention on the outcome of these patients would help in confirming the possible benefit of detecting subclinical motor-unit loss in CTS.
Keywords: carpal tunnel syndrome; motor-unit number estimation; motor nerve involvement